Skeletal abnormalities are common features in Ayme-Gripp syndrome - Niceta, Marcello; Barbuti, Domenico; Gupta, Neerja; Ruggiero, Carlos; Tizzano, Eduardo F.; Graul-Neumann, Luitgard; Barresi, Sabina; Nishimura, Gen; Valenzuela, Irene; Lopez-Grondona, Fermina; Fernandez-Alvarez, Paula; Leoni, Chiara; et al. (Clinical Genetics, 2019)
Ayme-Gripp syndrome (AYGRPS) is a recognizable condition caused by a restricted spectrum of dominantly acting missense mutations affecting the transcription factor MAF. Major clinical features of AYGRPS include congenital cataracts, sensorineural hearing loss, intellectual disability, and a distinctive flat facial appearance. Skeletal abnormalities have also been observed in affected individuals, even though these features have not been assessed systematically. Expanding the series with four additional patients, here we provide a more accurate delineation of the molecular aspects and clinical phenotype, particularly focusing on the skeletal features characterizing this disorder. Apart from previously reported malar flattening and joint limitations, we document that carpal/tarsal and long bone defects, and hip dysplasia occur in affected subjects more frequently than formerly appreciated.
CRIS-Team WoS Importer:2019-11-15